The Role of Urban Green Space in Promoting Inclusion: Experiences From the Netherlands - De Haas, Wim; Hassink, Jan; Stuiver, Marian (Frontiers in Environmental Science, 2021)
Urban Green Space (UGS) is considered to be beneficial for health and wellbeing of urban residents. But there is growing evidence these benefits are not equally distributed. In this article we aim to understand the role that UGS play in the process of social exclusion and the role urban greening strategies can play in enhancing social equity for specific groups that are excluded: elderly people with dementia, people with mental issues and people from an underprivileged neighborhood. The concepts of inclusion and exclusion and their relation to UGS are discussed. Four exclusion mechanisms are distinguished based on the role of the physical and societal environment and on the role of actors involved (public or private). Further, we identify four discourses behind possible strategies and measures to promote inclusion. These mechanisms and discourses are confronted with an analysis of three cases promoting inclusion of elderly with dementia, people with mental issues and people from an underprivileged neighborhood. The success of these cases is based on good cooperation between private actors initiative and public actors . The cases indicate that public and private actors need to cooperate better in order to make UGS part of inclusion strategies.